International Criminal Law and the Violence against Migrants - Ioannis Kalpouzos (German Law Journal, 2020)
Should we use the language of international criminal law (ICL) to discuss, analyze, and address Western policies of migration control? Such policies have included or resulted in indefinite and inhumane detention, deportations, including through practices of push- and pull-backs and numerous deaths of migrants attempting to cross land or sea borders. And yet, recourse to ICL's conceptual and rhetorical apparatus, often reserved for “unimaginable atrocities,” may seem ill-fitting and an emotive stretch of doctrine. Drawing from international strategic litigation practice on Australian and European policies, this article examines whether the legal concept of crimes against humanity can apply to the deaths, detention, and deportation of migrants, as part and consequence of Western policies of migration control. As migration control policies involve increasingly sophisticated practices of outsourcing and responsibility avoidance, I further ask whether the tools ICL has developed to describe system criminality can trace individual liability against the distance created by such policies. I also inquire into the potential that the transnational nature of migration and the spreading of anti-migration policies have in activating the jurisdiction of courts and the prioritization of the role of the International Criminal Court. Finally, I consider the danger of fetishizing an international punitive approach, before offering some thoughts that aim to bridge a critical approach to international criminal law with its use in meaningful strategic litigation. Throughout the Article, I argue that applying the categories of ICL to Western policies of migration control can contribute to revealing both the potential and the limits of the regime and its institutions, as well as the structures of asymmetry and injustice present both in anti-migration policies and in international criminal law itself.